Methotrexate: A detailed review on drug delivery and clinical aspects - Khan Z.A.; Tripathi R.; Mishra B. (My University, 2025)
Uses of methotrexate (MTX) are well established for the treatment of various types of malignancy, psoriasis, rheumatological diseases and the medical termination of pregnancy. Formulation and targeting approaches for MTX with controlled release carriers, multiparticulate systems, prodrug and drug conjugates have been found to improve bioavailability, reduce adverse effects and maximize clinical efficacy, compared with conventional methods. Areas covered: This exhaustive literature survey on different electronic databases covers drug delivery and clinical trials on MTX. This review deals with the challenges and achievements of controlled release, multiparticulate, prodrug and drug conjugate systems of MTX. Expert opinion: Therapeutic drug monitoring of MTX is crucial to attain a good efficacy. In spite of the advantages of multiparticulate, prodrug and drug conjugates, clinical applications of such formulations of MTX are still under infancy. These drug delivery systems require the special attention of medical experts for its wider clinical usage, and pharmaceutical experts for its scale-up. The combination of MTX with other antineoplastic and immunosuppressants should also be subjected to clinical trials, such as the combination of misoprostol with MTX in abortion. © 2012 Informa UK, Ltd.